1999
DOI: 10.1016/s0969-2126(00)80032-5
|View full text |Cite
|
Sign up to set email alerts
|

Binding of non-catalytic ATP to human hexokinase I highlights the structural components for enzyme–membrane association control

Abstract: The binding of AMP-PNP to a protein site separated from the catalytic centre of human hexokinase I can be related to the role played by some nucleotides in dissociating the enzyme from the mitochondrial membrane, and helps in defining the molecular regions of hexokinase I that are expected to be in contact with the mitochondrion. The structural information presented here is in keeping with monoclonal antibody mapping of the free and mitochondrion-bound forms of the enzyme, and with sequence analysis of hexokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 50 publications
3
48
0
Order By: Relevance
“…More specifically it belongs to the "actin-like ATPase domain" superfamily of proteins, often referred to as the ASKHA (acetate and sugar kinase/hsp70/actin) superfamily (8,23). Proteins in this superfamily include the ATPase domain of actin (22,29) and hsp70 (19), acetate kinase (11), several sugar kinases, such as hexokinase (44,48), glycerol kinase (24), ATP-and ADP-dependent glucokinases (25,35), as well as 2-hydroxyglutaryl-CoA dehydratase component A (2-HG-CoA dehydratase Comp A) (33). Similar to all other members of the ASKHA superfamily, the PanK Tm monomer contains two domains that have the same fold and are considered to be a result of gene duplication (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…More specifically it belongs to the "actin-like ATPase domain" superfamily of proteins, often referred to as the ASKHA (acetate and sugar kinase/hsp70/actin) superfamily (8,23). Proteins in this superfamily include the ATPase domain of actin (22,29) and hsp70 (19), acetate kinase (11), several sugar kinases, such as hexokinase (44,48), glycerol kinase (24), ATP-and ADP-dependent glucokinases (25,35), as well as 2-hydroxyglutaryl-CoA dehydratase component A (2-HG-CoA dehydratase Comp A) (33). Similar to all other members of the ASKHA superfamily, the PanK Tm monomer contains two domains that have the same fold and are considered to be a result of gene duplication (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A search for similar structures by using the DALI server (29; http://www.ebi.ac.uk/dali/) found that the most similar structures were human brain hexokinase I (PDB code 1QHA) (57) and hexokinase B (also known as hexokinase PII) from S. cerevisiae (PDB 2YHX) (4). Yeast hexokinase PII is somewhat larger than ecGlK, comprising 486 residues (38), while human hexokinase type I is much larger, consisting of two ϳ50-kDa chains (72).…”
Section: Resultsmentioning
confidence: 99%
“…Several crystal structures of hexokinases have been determined, including hexokinase A(PI) (10) and B(PII) (4,38), both from Saccharomyces cerevisiae, rat type I and Schistosoma mansoni hexokinase (46), human brain type I (1,2,3,57), and, recently, human type IV (glucokinase) (36). Only three microbial ADP-dependent GlK structures are available, all from sequence group I.…”
mentioning
confidence: 99%
“…X-ray crystallographic structures of HKI are available (11)(12)(13)(14)(15). The wild-type enzymes are dimers of 100 kDa subunits (12), but an engineered mutant HKI crystallizes as a monomer, adopting a conformation similar to that of the subunit of the dimer (14).…”
mentioning
confidence: 99%